Consumer culture - Lury, Celia (Cambridge : Polity Press, 1996)
This book is about: The stuff of material culture; Material culture and consumer culture; The stylization of consumption; ...
Keywords: Culture; Consumption; Consumer behavior; Consumption (Economics) -- Social aspects; Culture -- Economic aspects